2022
DOI: 10.1111/jbg.12723
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution genomic analysis of four local Vietnamese chicken breeds

Abstract: Vietnam is an agricultural country, with 70% of the human population living in rural areas (Desvaux, Vu Dinh, Phan Dang, & Pham Thi, 2008). In these areas, nearly 50%-90% of households own livestock (Burgos, Hong Hanh, Roland-Holst, & Burgos, 2007). Moreover, according to Ngoc (2020), approximately 7,864,700 households raised poultry in 2019. Local chickens in Vietnam account for over 70% of the national poultry population (Lan Phuong, Dong Xuan, & Szalay, 2015). There are 21 local chicken breeds, of which Ri,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The diversity indices in the 2 local populations were quite similar to the range reported for Italian ( Strillacci et al, 2017 ; Cendron et al, 2020 ), European ( Malomane et al, 2019 ), and other native chicken populations ( Evelyne et al, 2022 ; Yuan et al, 2022 ; Wang et al, 2023 ). However, the values differed from the results of a previous study ( Cendron et al, 2020 ), in which the authors reported lower values of heterozygosity and higher values of inbreeding for Cornuta di Sicilia and Val Platani populations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The diversity indices in the 2 local populations were quite similar to the range reported for Italian ( Strillacci et al, 2017 ; Cendron et al, 2020 ), European ( Malomane et al, 2019 ), and other native chicken populations ( Evelyne et al, 2022 ; Yuan et al, 2022 ; Wang et al, 2023 ). However, the values differed from the results of a previous study ( Cendron et al, 2020 ), in which the authors reported lower values of heterozygosity and higher values of inbreeding for Cornuta di Sicilia and Val Platani populations.…”
Section: Discussionsupporting
confidence: 79%
“…The evaluation of local genetic resources involves records of phenotypes, the investigation of their breeding history, as well as the study of genetic variability both within and between populations ( Wimmers et al, 2000 ). Population genetic analyses can help explain the evolutionary history of these animals, clarify the origin and differentiation of populations, and assist in genetic breeding ( Elbeltagy et al, 2016 ; Fleming et al, 2016 ; Cendron et al, 2020 ; Evelyne et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have drawn similar conclusions ( Cuc et al, 2010 ), while Vietnamese chicken breeds could be better separated at higher K values. The divergence of Vietnamese chicken breeds is closely related to their geographical distribution ( Evelyne et al, 2022 ). Northern chicken breeds comprise an unstructured gene pool, and differentiation of Vietnamese chicken breeds can be observed between the northern and south-central coasts, as well as the Mekong Delta ( Cuc et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%